In Silico Study of Phytoconstituents of Moringa Oleifera Against Trehalose–6–Phosphate Phosphatase (TPP) Enzymes - Payal Bhatnagar; Neha Dangi (Current Research in Pharmaceutical Sciences, 2023)
Numerous pathogenic microorganisms use the enzymes trehalose-6-phosphate phosphatase (TPP) to biosynthesize the sugar trehalose from trehalose-6-phosphate (T6P) as part of their infection and proliferation processes. In order to build new generation candidate medications to inhibit TPP using in silico approaches, the current work is being done. The majority of the 10 phytochemicals from Moringa oleifera that were used in docking studies with the 3D model of TPP had good binding affinities to the enzyme, with campesterol and stigmat-4-en-3-one showing the highest affinities (Binding energies of - 7.8 kcal/mole and -8.0 kcal/mole, respectively), when compared to the commonly used commercial drug isoniazid (Binding energy of –6.0 kcal/mole).The active site of TPP sequences, which coordinates Mg2+ and is necessary for catalysis, has been discovered to bind to phytochemical leads during docking. Binding poses and distance measurement of TPP-phytochemical complexes of 5-Hydroxymethylfurfural, Citronellol, Xylitol, 2,4-Di-tert-butylphenol, Palmitoleic acid, cis-Vaccenic acid, Phytol, Cyclopentane, 1,1-[3-(2-cyclopentylethyl)-1,5-pentanediyl]bis-, Campesterol and Stigmat-4-en-3-one reveals that the lead phytochemicals were in close proximity with most of the active site amino acids (distance range from 1.88 to 3.77 Aº). This demonstrates the close affinity between the enzyme and the leads, which may open the door to the development of new generation medications to treat diseases caused by pathogenic microorganisms that produce TPP.